PENGARUH JUMLAH PENDUDUK, LUAS LAHAN DAN UPAH MINIMUM KABUPATEN/KOTA TERHADAP JUMLAH PENERIMAAN PAJAK BUMI DAN BANGUNAN - Hoziah, Siti Nur; Handayani, Henni Rahayu (Jurnal Nusa Akuntansi, 2025)
This research aims to determine the effect of population size, land area, and district/city minimum wages. The population in this research is the sub-districts in Depok City in 2018-2022. The type of research used is a quantitative approach. The sampling technique in this research used a purposive sampling method and obtained samples from 11 sub-districts with a total of 55 research samples. The data analysis technique used is multiple linear regression using E-views 12 software. The results of the analysis show that the sig t value of the population is 0.0064 <0.05, this result means that the population has a partial effect on PBB revenue, and the sig t value of land area is 0.1019 > 0.05, this result means that land area does not have a partial effect on PBB revenue, while the sig t value of the city minimum wage is 0.0000 <0.05, this means that the city minimum wage has a partial effect on PBB revenue. Simultaneously, the sig f value is 0.0000 <0.05, which means that together the population, land area, and city minimum wage have an effect on PBB revenue.